Trace elements in bone of Zalophus californianus from the Gulf of California: A comparative assessment of potentially polluted areas - Diana Szteren; David Aurioles-Gamboa (Ciencias Marinas, 2013)
As a top predator, California sea lions (Zalophus californianus) can be used as sentinels to record ecosystem conditions because of the trace metals that bioaccumulate in their tissues and are biomagnified in the trophic webs. The concentration of 11 trace elements (Al, As, Cd, Co, Cu, Fe, Hg, Ni, Pb, Se, and Zn) was measured in California sea lion skulls from four regions of the Gulf of California (Mexico): Northern Gulf, Ángel de la Guarda, Central Gulf, and Southern Gulf. The aims of this study were (1) to determine and compare the mean concentration of trace elements among the four regions, and (2) to estimate the pollution situation of each region using the more toxic trace elements. The elements found in higher concentration in sea lion bone were Al (overall mean of 73.70 µg g–1) and Zn (60.78 µg g–1). Only the concentration of As and Hg showed significant differences among regions: As was higher in the Central Gulf than in Ángel de la Guarda and the Northern Gulf, while Hg was higher in the Northern Gulf and Ángel de la Guarda than in the Central and Southern Gulf. The comparative analysis of the pollution situation indicated that the Central Gulf was the most affected by As and Cd, and the Northern Gulf and Ángel de la Guarda by Hg. Regions with different trace element concentrations may reflect different feeding habits and oceanographic conditions, and are congruent with other regional patterns suggested for the Gulf of California.